PENGARUH DIGITAL MARKETING, VARIASI PRODUK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN AYAM GEPREK JODER KA DHANI DI SURABAYA TIMUR. - _, Mahesin; Pratiwi, Ni Made Ida; Pujianto, Agung (Jurnal Dinamika Administrasi Bisnis, 2025)
The fast food industry that provides the main menu of fried chicken in Indonesia, or more precisely, located in East Surabaya, is not only Joder Ka Dhani. So business actors are of course faced with the problem of intense competition which of course cannot be avoided and requires business actors to have the main weapon to be able to attract consumer purchasing decisions. Several factors that business actors can use to influence consumers in making purchasing decisions are by looking at current trends in marketing such as digital marketing, providing various product choices and paying attention to product quality. This research aims to analyze the influence of digital marketing, product variety and product quality on purchasing decisions for Joder Ka Dhani geprek chicken in East Surabaya. The research method used was quantitative with a survey approach, using an e-questionnaire via Google Form which was distributed to 96 respondents who were Joder Ka Dhani Geprek Chicken consumers. The collected data was analyzed using multiple linear regression analysis to identify the relationship between these variables. The research results show that digital marketing, product variety and product quality have a significant positive influence on purchasing decisions at Ayam Geprek Joder Ka Dhani. These findings indicate that improvements in digital marketing strategies, product variety and product quality can significantly increase consumer purchasing decisions at Ayam Geprek Joder Ka Dhani. The implications of this research show the importance of continuous innovation in digital marketing strategies, making changes to product variations and improving product quality to maintain competitiveness and consumer purchasing decisions. This research makes an important contribution to the digital marketing literature, product variety and product quality, as well as providing practical guidance for other fried chicken business actors in developing effective marketing strategies.